Applied thin-layer chromatography [ best practice and avoidance of mistakes - Hahn-Deinstrop, Elke (Wiley-VCH, 2007)
Thin layer chromatography (TLC) is a powerful, fast and inexpensive analytical method. It has proven its usefulness in pharmaceutical, food and environmental analysis. In this illustrated book all steps of the analytical procedure are clearly explained, starting with the choice of a suitable TLC technique and ending with data evaluation and documentation. Special emphasis is put on the proper choice of materials for TLC. Properties and functions of various materials and the TLC equipment are described, covering e. g. precoated layers, solvents and developing chambers. Information on suppliers and many practical hints for trouble shooting are also included. How to use TLC in compliance with GLP/GMP regulations, as well as the required documentation, is also described in detail